Acoustic characteristics of a horizontal axis micro hydrokinetic turbine. (1st September 2022) - Wang, Xiu; Hu, Zhou-Ping; Yan, Yan; Pei, Junxian; Wang, Wen-Quan
Abstract: A micro hydrokinetic turbine is a device for extracting energy from rivers or tides, and this device represents one of the frontiers for renewable energy technology. A detailed analysis of the acoustic characteristics of these turbines is of great significance for their cleaner production, further development, and use. Based on the Ffowcs Williams and Hawkings integration method, the acoustic characteristics of the horizontal axis of a micro hydrokinetic turbine are numerically studied in this work, with emphasis on the acoustic distribution, the acoustic spectrum in the time and frequency domains, and the acoustic directivity in different regions. It is found that the noise of a horizontal axis micro hydrokinetic turbine mainly occurs at the leading edge and tip of the blade due to the appearance and separation of vortices at these locations. The noise signal is mainly caused by the blade passing frequency, especially the first-order frequency, and with the features of a low frequency and broad band. In the progress of downstream propagation, rapid energy dissipation leads to the gradual decrease of the sound pressure level. Furthermore, the noise radiation of the blade has obvious dipole characteristics in the flow direction. The results presented here will contribute to a fundamental understanding of the acoustic characteristics of a turbine. Highlights: High intensity noise sources are near the leading edge and tip of the blade. Acoustic pressure show obvious periodicity. Peak value of SPL is mainly located at the first order BPF and its harmonic frequency. Noise radiation of blade has an obvious dipole characteristic.